Screening of Workers with Presumed Occupational Methanol Poisoning: The Applicablility of a National Active Occupational Disease Surveillance System - Huisu Eom; Jihye Lee; Eun-A Kim (Safety and Health at Work, 2019)
Background: Methyl alcohol poisoning in mobile phone–manufacturing factories during 2015–2016 was caused by methyl alcohol use for cleaning in computerized numerical control (CNC) processes. To determine whether there were health complications in other workers involved in similar processes, the Occupational Safety and Health Research Institute conducted a survey. Methods: We established a national active surveillance system by collaborating with the Ministry of Employment and Labor and National Health Insurance Service. Employment and national health insurance data were used. Overall, 12,048 employees of major domestic mobile phone companies and CNC process dispatch workers were surveyed from 2016 to 2017. We investigated methyl alcohol poisoning by using the national health insurance data. Questionnaires were used to investigate diseases due to methyl alcohol poisoning. Results: Overall, 24.9% of dispatched workers were employed in at least five companies, and 23.9% of dispatched workers had missing employment insurance history data. The prevalence of blindness including visual impairment, optic neuritis, visual disturbances, and alcohol toxicity in the study participants was higher than that reported in the national health insurance database (0.02%, 0.07%, 0.23%, and 0.03% versus 0.01%, 0.07%, 0.13%, and 0.01%, respectively, in 2015). Moreover, 430 suspicious workers were identified; 415 of these provided an address and phone number, of whom 48 responded (response rate, 11.6%). Among the 48 workers, 10 had diseases at the time of the survey, of whom 3 workers were believed to have diseases related to methyl alcohol exposure. Conclusion: This study revealed that active surveillance data can be used to assess health problems related to methyl alcohol poisoning in CNC processes and dispatch workers. Keywords: Dispatched workers, Methyl alcohol, Mobile phone, Occupational disease surveillance system, Visual disturbance